Microwave‑assisted pyrolysis: A review of tailored carbon materials and scale‑up challenges - Wong, Pin Shern; Chong, William Woei Fong; Tan, Jian Ping; Nur Aisya Affrina Mohamed Ariffin; Foo, Chuan Yi; Rubia Idris; Woon, Kok Sin; Wong, Keng Yinn; Tee, Wei Hown; Mong, Guo Ren (Elsevier, 2025)
Microwave-assisted pyrolysis (MAP) has emerged as a transformative method to synthesize high-value carbon materials from diverse waste feedstocks, offering rapid heating rates (up to 330 °C/s) and potentially reducing the process’s activation energy. This review systematically evaluates MAP-derived solid carbon products such as biochar, activated carbon, carbon nanotubes (CNTs), carbon dots, and carbon onions (CNOs), highlighting their tailored properties for advanced applications. Key innovations include biochar with a BET surface area of 419 m²/g for NH₃ adsorption (66.6 % removal efficiency), activated carbon supercapacitors achieving 48.2 Wh/kg energy density, and nitrogen-doped CNTs with oxygen reduction reaction (ORR) performance comparable to commercial Pt/C catalysts. Despite these advances, technical challenges such as non-uniform temperature distribution, material compatibility in scaled reactors, and energy efficiency trade-offs continue to hinder industrial adoption. This work identifies pathways to optimize microwave parameters such as frequency modulation, and proposes recommendations for temperature measurement techniques. Notably, this article outlines potential practical strategies that offer a path to bridge the gap between laboratory-scale insights and the demands of industrial-scale implementation, positioning MAP as a sustainable platform for carbon material synthesis.